IMPLEMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Lana Sugiarti; Ricardus Jundu; Dorotea Yuinasti (UNZAH Genggong, 2023)
This study aims to compare the mathematical problem solving abilities of students who are taught using the problemc based learning model and the mathematical problem solving abilities of students who are taught using conventional learning models in class VII students of SMP Negeri 18 Satarmese in the 2022/2023 academic year.Pretestposttest control group design is used in the quasi-experimental design of the research. There were a total of 58 students in class VII at SMP Negeri 18 Satarmese who participated in this study. Sampling in this used non-probability sampling or a sampling technique that did not provide equal opportunities or opportunities for each elemnt or member of the population to be selected as a sample, so the researchers made class VII A as the experimental class and class VII B as the control totaling 29 participants. A description-based mathematical problem solving ability test was used to gather the information. Prerequisite tests, such as homogeneity and normality tests, were carried out prior to the analysis of the data. The data from both groupd come from a population that is normally distributed and has a homogeneous variance, as demonstrated by the calculations for the normality and homogeneity tests. Then a hypothesis test was AL-FIKRU: JURNAL PENDIDIKAN DAN SAINS, 4 (1), 2023 | e-ISSN 2774-5627 p-ISSN 2747-134948carried out to see the studentd’ mathematical problem solving abilities. The N-gain score data were the ones that were analyzed using the independent t test statistical method.Based on the data analysis result obtained that the calculation result = 8,03 and = 1,67 at the significant level and degrees of freedom. Because price = 8,03 > price = 1,67, it is accepted and rejected. Therefore, there are differences in students mathematical problem solving abilities taught using the Problem Based Learning model with students mathematical problem solving abilities taught using conventional models. Based on the research results, recommendations for further research are to carry out similar research with other learning models and other classes.Keywords: Conventional Learning, the Problem Based Learning (PBL) model, the ability to solve Mathematical Problems